Sports training in summer polyathlon based on the rational distribution of training loads - Nikiforova, O. N.; Markin, E. V.; Sorokin, D. V.; Khoteeva, M. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the rationality of the distribution of training loads of different types of all-around exercises of polyathlon students in the annual cycle.